The synergy of TPL and selinexor in MLL-R acute myeloid leukemia via Rap1/Raf/MEK pathway-mediated MYC downregulation - Manman Deng; Peicui Huang; Lijuan Wang; Yuelong Jiang; Zhenling Guo; Hongpeng Duan; Jie Zha; Haijun Zhao; Guowei Li; Bing Xu (Translational Oncology)
MLL gene rearrangement recurrently occurs in acute myeloid leukemia (MLL-r AML), which is closely associated with chemotherapy insensitivity and unfavorable clinical outcomes. More importantly, there are limited therapeutic options for the management of patients with MLL-r AML, thus necessitating novel effective treatment strategies. In this study, we demonstrated that low doses of triptolide (LD TPL) and the XPO1 inhibitor selinexor exerted synergistic therapeutic effects on poor-outcome MLL-r AML in vitro, ex vivo and in vivo. Induction of mitochondrial outer membrane permeabilization (MOMP) and initiation of the mitochondrial apoptotic pathway were closely involved in the therapeutic synergy of LD TPL in combination with selinexor against MLL-r AML. Mechanistically, MYC downregulation mediated by the Rap1/Raf/MEK/ERK pathway rather than by PI3K/AKT signaling was implicated in the synergistic activity of the combined regimen. In addition, the induction of DNA damage also contributed to the synergistic effects of the combined regimen on MLL-r AML. In summary, our findings suggest that LD TPL in combination with selinexor might represent a promising therapeutic approach for the treatment of MLL-r AML. However, future clinical trials are mandatory to draw a decisive conclusion.